Evaluating the Three-Phase Computer Literacy Training Program for Alternative Learning System Students: A Comprehensive Analysis of the Pagpabakud kang Kinaaram Paagi sa Teknolohiya Initiative - Española Jr, Alberto M.; Eraga, Maricel A.; Yumen, Maria Odessa Y.; Yumen, Jovie J. (REVIEW OF MULTIDISCIPLINARY EDUCATION, CULTURE AND PEDAGOGY, 2025)
This comprehensive study evaluates the effectiveness and impact of the three-phase "Pagpabakud kang Kinaaram Paagi sa Teknolohiya" (Advancing Knowledge Through Technology) computer literacy training program implemented for Alternative Learning System (ALS) students in the District of Tibiao, Antique, Philippines from 2017 to 2024. The study analyzes three distinct phases of the program, examining their evolution, implementation strategies, and outcomes across different cohorts over a seven-year period. Using a mixed-methods longitudinal approach, this research assessed the program's effectiveness in enhancing digital literacy skills, promoting gender equality awareness, and improving educational outcomes among ALS learners. Data was collected from 205 ALS participants across all three program phases, with evaluation metrics including skill acquisition assessments, participant feedback, and post-training impact analysis. Results demonstrate significant improvements in Microsoft Office proficiency (68-75% improvement rates), computer handling skills (80% improvement), and digital literacy competencies. The program successfully evolved from basic IT skills training to comprehensive digital citizenship education, expanding from 3 Sustainable Development Goals (SDGs) in Phase I to 4 SDGs in Phase III, particularly Quality Education (SDG 4), Gender Equality (SDG 5), and Reduced Inequalities (SDG 10). The study reveals the critical importance of sustained, phase-based approaches to digital literacy education in alternative learning contexts, providing valuable insights for educational policy and program design in developing countries.